How Adopting New Performance Measures Affects Subjective Performance Evaluations: Evidence from EVA Adoption by Chinese State-Owned Enterprises - Du, Fei; Erkens, David H.; Young, S. Mark; Tang, Guliang (The Accounting Review, 2018)
ABSTRACT This study investigates how adopting new performance measures affects the decision process through which supervisors make subjective adjustments. In our setting, the Chinese government substituted economic value added (EVA) for return on equity (ROE) in the performance score formula it uses to evaluate State-Owned Enterprises (SOEs). In accordance with the Chinese government's objective to increase the capital efficiency of SOEs, supervisors shifted the weight in subjective adjustment decisions from ROE to EVA after EVA adoption. Consistent with EVA adoption creating fairness concerns, however, supervisors did not penalize SOEs for performing poorly on EVA when they performed well on ROE, and accomplished this by shifting the weight from EVA back to ROE. Additional analyses suggest that personal preferences motivated supervisors to make these lenient subjective adjustments. Overall, our findings indicate that adopting new performance measures creates fairness concerns that motivate supervisors to consider their personal preferences in subjective adjustment decisions.